Interventions promoting breast cancer screening among turkish women with global ımplications: a systematic review - Güneş, Güssün; Seçginli, Selda; Nahçıvan, Nurşen; Fernandez, Ritin (My University, 2017)
Background: Breast cancer is a major health concern and remains the most common malignancy inwomenworldwideandinTurkey.Mammography,clinicalbreastexamination(CBE),andbreast self-examination (BSE) are recommended methods to detect early breast cancer in women. Many strategies have been developed to increase the rates of mammography, CBE, and BSE among Turkish women. Despite the beneﬁts of breast cancer screening, these modalities are still underutilized by the majority of Turkish women. Aim: To systematically review the scientiﬁc evidence on the effectiveness of various strategies aimed at improving screening behaviors for breast cancer in Turkish women. Methods: A systematic review of the literature published between 2000 and 2015 was conducted, searching 10 databases of Ovid MEDLINE, PubMed, Cochrane CENTRAL Register of Controlled Trials, CINAHL, PsycINFO, Web of Knowledge, Scopus, Google Scholar, ULAKBIM Turkish Medical Database, and Council of Higher Education Thesis Center. Results: Twenty-three studies were included in the ﬁnal review. The majority of the studies investigated the effects of multiple strategies to improve BSE. Group education comprised educational sessions, printed and audiovisual materials, which signiﬁcantly improved BSE, CBE, and mammography screening rates at 3 months, 6 months, and 12 months after the intervention. One-to-one education demonstrated no signiﬁcant difference in BSE rates at 6-month and 12-monthfollow-up.However,one-to-oneeducationdemonstratedsigniﬁcantdifferencesinCBE and mammography rates at the 3-month follow-up. Linking Evidence to Action: The use of group education comprising a multicomponent intervention demonstrated an increase in breast-screening behaviors among Turkish women. Further research investigating the duration of educational interventions is needed in order to suggest a “dose response.”
Keywords: systematic review, intervention, breast self-examination, clinical breast examination, mammography, Turkish women